A systematic review of recall errors associated with portion size estimation aids in children. (1st April 2020) - de Vlieger, N.M.; Weltert, M.; Molenaar, A.; McCaffrey, T.A.; Rollo, M.E.; Truby, H.; Livingstone, B.; Kirkpatrick, S.I.; Boushey, C.J.; Kerr, D.A.; Collins, C.E.; Bucher, T.
Abstract: To reduce errors in portion size estimation, a number of aids have been developed and tested. This systematic review synthesizes what is known about error associated with use of different portion size estimation aids (PSEAs) within self-reported dietary recall studies in children (aged ≤18 years). Eight electronic databases were searched using relevant keywords. From 8184 records identified and screened, 327 full texts were retrieved, with 10 records representing 9 studies meeting inclusion criteria. Studies using proxy reporting were excluded. Thirteen PSEAs were identified. To facilitate comparisons between different types of aids they were categorized into 'physical 2-dimensional (2D)', 'digital 2D' and '3-dimensional' PSEAs. Seven were physical 2D (e.g. food atlas), two were digital 2D (i.e. computer-based), and four were 3D (e.g. modelling clay, household items). Comparisons of PSEAs within studies found the smallest estimation errors for digital 2D and largest for 3D aids. Errors in relation to food type were varied, with portions of amorphous foods overestimated in multiple studies. No effects for recall interval time or sex were identified. One study reported a significant improvement in estimation error with increasing age. Across studies, large variations in study design and reporting of estimation error hindered the synthesis of evidence regarding the influence of different types of PSEAs on accuracy. While a definitive conclusion about the most accurate PSEA could not be drawn, a check-list to guide future PSEA development and testing has been proposed in the current review. This will assist comparability with future studies of PSEAs for children facilitate development of more accurate PSEAs in the future.